An update on epilepsy. (May 2011) - Schoenberg, Mike R; Frontera, Alfred T; Bozorg, Ali; Hernandez-Frau, Pedro; Vale, Fernando; Benbadis, Selim R
The understanding of seizures and epilepsy as a disease has accelerated to reflect advances in the understanding of the interplay of seizures and epilepsy on neurophysiology, neuroplasticity, sleep, neuropsychology, behavior and social functioning of the individual, which interact with and can be affected by an individual''s quality of life, educational development and occupational success. Updates in the treatment of status epilepticus, epilepsy in children and adults (particularly women), and psychogenic nonepileptic seizures/attacks have been announced. There is increasing emphasis on untangling the interactive forces of new antiepileptic medications from epilepsy/seizures on the neurophysiological, neuropsychologic and psychiatric/behavioral functioning of individuals with epilepsy. The role of GABA in the pathophysiology of seizures and status epilepticus has led to novel therapy proposals. Neurostimulation technologies and neurosurgical procedures have improved the clinical outcomes of patients with epilepsy, and have led to important advances in understanding the neuropathophysiology of epilepsy/seizures and brain plasticity. For example, neurostimulation allows long-term in vivo electroneurophysiological recordings of specific brain regions that has not been previously possible in humans. The 64th Annual Meeting of the American Epilepsy Society and the 3rd Biennial North American Regional Epilepsy Congress provided state-of-the-art updates to scientific and clinical practice issues in the treatment of epilepsy.